Targeting miR‐223 in neutrophils enhances the clearance of Staphylococcus aureus in infected wounds. Issue 10 (31st August 2018) - de Kerckhove, Maiko; Tanaka, Katsuya; Umehara, Takahiro; Okamoto, Momoko; Kanematsu, Sotaro; Hayashi, Hiroko; Yano, Hiroki; Nishiura, Soushi; Tooyama, Shiho; Matsubayashi, Yutaka; Komatsu, Toshimitsu; Park, Seongjoon; et al.
Abstract: Argonaute 2 bound mature microRNA (Ago2‐miRNA) complexes are key regulators of the wound inflammatory response and function in the translational processing of target mRNAs. In this study, we identified four wound inflammation‐related Ago2‐miRNAs ( miR‐139‐5p, miR‐142‐3p, miR‐142‐5p, and miR‐223 ) and show that miR‐223 is critical for infection control. miR‐223 Y /− mice exhibited delayed sterile healing with prolonged neutrophil activation and interleukin‐6 expression, and markedly improved repair of Staphylococcus aureus ‐infected wounds. We also showed that the expression of miR‐223 was regulated by CCAAT/enhancer binding protein alpha in human neutrophils after exposure to S. aureus peptides. Treatment with miR‐223 Y /− ‐derived neutrophils, or miR‐223 antisense oligodeoxynucleotides in S. aureus ‐infected wild‐type wounds markedly improved the healing of these otherwise chronic, slow healing wounds. This study reveals how miR‐223 regulates the bactericidal capacity of neutrophils at wound sites and indicates that targeting miR‐223 might be of therapeutic benefit for infected wounds in the clinic. Synopsis: In this study, miR‐223 is identified as a major player for infection control during wound inflammatory response. miR‐223 regulates the bactericidal capacity of neutrophils at wound sites, and targeting miR‐223 might be of therapeutic benefit for infected wounds in the clinic. miR‐223, miR‐142‐3p, miR‐142‐5p, and miR‐139‐5p were expressed upon wound inflammation. miR‐223 is critical for neutrophils activation and subsequent resolution of the acute inflammatory response in wound sites. Upon stimulation with S. aureus peptides, IL‐6 secretion is regulated by the C/EBPα‐miR‐223 signaling pathway. Cell transplantation therapy using miR‐223‐deficient neutrophils or miR‐223 antisense oligodeoxynucleotide knockdown in wounds improved the healing of S. aureus ‐infected WT wounds. Abstract : In this study, miR‐223 is identified as a major player for infection control during wound inflammatory response. miR‐223 regulates the bactericidal capacity of neutrophils at wound sites, and targeting miR‐223 might be of therapeutic benefit for infected wounds in the clinic.